Do Faculty and Gender Matter to Students’ English Proficiency Score? - Azkiyah, Siti Nurul (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
AbstractIt is undeniable that English is an important international language and there could be some background variables influencing English proficiency. Therefore, UIN Syarif Hidayatullah Jakarta as the context of the study regulates that all students take an English proficiency test once they are accepted and must achieve 450 for non-English departments and 500 for English studies before they graduate. Having 12 faculties of Islamic and non-Islamic studies, it is interesting to measure whether faculty as a background variable matters. In addition, female as another background variable has been widely found to have better achievement in language, and therefore this study is also intended to investigate whether gender is a contributing factor to students’ English proficiency. The population was all students of UIN Jakarta year 2017, which data of 5089 students’ English proficiency scores, faculties, and gender were collected through the information technology center. The descriptive analysis reveals that the lowest score is 240 while that highest one is 570 and the mean score is 383. The ANOVA analysis reports significant differences among faculties: the Faculty of Medicine achieves the highest score (M = 429) while the Faculty of Ushuluddin attains the lowest (M = 365). In addition, female students, as yielded by t-test analysis, are found to have significantly higher English proficiency score. The findings implies the need to pay more attention to Islamic-related faculties having lower scores and to consider English proficiency score as an enrolment requirement especially for the faculty of Medicine. AbstrakTidak bisa dipungkiri bahwa Bahasa Inggris sangat penting dan ada beberapa faktor yang berpengaruh terhadap kecapakan berbahasa Inggris. Oleh karena itu, UIN Syarif Hidayatullah Jakarta sebagai konteks studi ini mewajibkan semua mahasiswa yang diterima untuk mengikuti tes kecakapan berbahasa Inggrisd dan harus mencapai skor 450 untuk mahasiswa di luar prodi Bahasa Inggris dan 500 untuk prodi Bahasa Inggris sebelum mereka lulus. Dengan 12 fakultas baik studi Islam maupun non-Islam, menjadi menarik untuk melihat apakah fakultas sebagai sebuah variabel memiliki pengaruh. Selain itu, jender (perempuan) sebagai variabel lain sudah banyak ditemukan oleh studi lain memiliki prestasi yang lebih unggul dalam kecakapan berbahasa, dan oleh karena itu studi ini juga bertujuan untuk mengukur apakah gender merupakah faktor yang berpengaruh terhadap kecapakan berbahasa Inggris. Populasi studi ini adalah mahasiswa UIN Syarif Hidayatullah Jakarta angkatan 2017, di mana data skor English Proficiency Test, asal fakultas dan jender sejumlah 5089 mahasiswa berhasil dikumpulkan dan Pustipanda. Dari analisis deskriptif statistik ditemukan bahwa skor terendah adalah 240 sedangkan tertinggi adalah 570 dan nilai rata-ratanya sebesar 383. Hasil analisis ANOVA menunjukkan adanya perbedaan yang signifikan diantara fakultas, di mana Fakultas Kedokteran memiliki nilai rata-rata tertinggi (429) sementara Fakultas Ushuluddin memiliki nilai rata-rata terendah (365). Mahasiswa (perempuan), sebagaimana ditunjukkan oleh hasil analisis t-test, memiliki nilai rata-rata yang secara signifikan lebih tinggi dibanding mahasiswa (laki-laki).How to Cite : Azkiyah, S.,N. (2018). Do Faculty and Gender Matter to Students’ English Proficiency Score?. TARBIYA: Journal of Education in Muslim Society, 5(2), 116-125. doi:10.15408/tjems.v5i2.1667.